Reliability Between Sarcopenia Diagnosis by EWGSOP 1 and EWGSOP 2 Criteria and Association With Clinical Parameters in Maintenance Hemodialysis Patients - Guimarães, Laura Tavares; Silva, Maryanne Zilli Canedo da [UNESP]; Reis, Nayrana do Carmo Soares [UNESP]; Caramori, Jacqueline Costa Teixeira [UNESP]; Vogt, Barbara Perez (Elsevier, 2025)
Objectives: To analyze the reliability between the sarcopenia criteria proposed by the European Working Group on Sarcopenia in Older People (EWGSOP) 1 and 2 and to verify the association of clinical parameters with sarcopenia diagnosis in patients on maintenance hemodialysis. Methods: Cross-sectional analysis including adult patients on maintenance hemodialysis. The assessment of lean mass was performed by dual-energy X-ray absorptiometry, and the appendicular lean mass index was calculated. The assessment of muscle strength was performed using a handgrip dynamometer. The cutoff values considered for sarcopenia diagnosis were proposed by the EWGSOP 1 and EWGSOP 2 criteria. Results: 124 patients were included. The frequency of sarcopenia diagnosis was higher according to EWGSOP 1 (25.8%) than according to EWGSOP 2 (12.9%). The frequency of sarcopenia diagnoses diminished in both sexes. The reliability between the two criteria was moderate (κ = 0.597; P < .001), and 87.1% of patients were classified equally by both criteria. In EWGSOP 1, the presence of diabetes and serum iron was significantly higher in the group with sarcopenia, and in EWGSOP 2 there was no such difference. Conclusion: The frequency of sarcopenia diagnosis in patients on hemodialysis was higher by EWGSOP 1 compared to EWGSOP 2, and the reliability between the criteria was moderate. Sarcopenia diagnosed by EWGSOP 1 was associated with diabetes and serum iron, which are factors that may be associated with sarcopenia pathogenesis. EWGSOP 2 was not associated with the clinical parameters assessed.
Keywords: chronic kidney disease; EWGSOP; handgrip strength; muscle strength; sarcopenia